Indonesia: Anti-communism in the age of reformasi: the case of Papernas - Hearman, Vannessa (2008)
In 2006, some long-term Indonesian activists in the People’s Democratic Party (PRD), such as Dita Sari and Agus ``Jabo’’ Priyono, reflected on how the post-1998 reformasi movement would respond to the 2009 general election. In June 2006, a number of activists and organisations, including eight national organisations such as the Indonesian Buddhist Students’ Association (HikmahBudhi), the National Students’ League for Democracy (LMND) and the Urban Poor Union (SRMK) met in Jakarta to agree to establish Papernas (the National Liberation Party of Unity). Around 40 local groups of farmers, workers, students and advocacy groups in Flores, Sumatra, Maluku, Java and Kalimantan also supported this initiative. PRD activists have made Papernas their key political project in the last few years, which also has created debates and splits inside the PRD over the question of electoral alliances in coming elections.